Fungsi Hadits Nabi Muhammad SAW terhadap Al-Qurâan - Sani, Mukhyar (Alhadharah: Jurnal Ilmu Dakwah, 2013)
The Quran is a holy book of Muslims, which contains the revelations of Allah. delivered to the Prophet Muhammad pbu. Its global content still needs clarity for people to be able to understand it properly. Prophet Muhammad pbu has authority to explain the unclear parts of the book through the Hadith or Sunnah. In this case, the books needs al-bayan, al-Tafsir al-tafshil, al-taqrir, perhaps even al-naskh derived from the prophet Muhammad pbu. He is acknowledged by the Quran as its "mubayyin". Therefore, the Hadith of the Holy Prophet Muhammad serves as the second source of Islamic teachings after the Quran. The scholars of ahl atsar and ahl rayi agreed that hadits explains the Quran. The scholars of ahl al-atsar expanded explained hadits, meanwhile ahl al-raâyi limited them. Fot the former, all true hadits about the problems mentioned in the al-Qurâan should be considered as explaining the Quran, specifying its generality, and limiting its absolute parts